On Lie Ideals and Generalized Jordan Left Derivations of Prime Rings - Ansari, A. Z.; Rehman, N. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let R be a prime ring with characteristic different from 2 and U be a Lie ideal of R. In the paper, we initiate the study of generalized Jordan left derivations on Lie ideals of R and prove that every generalized Jordan left derivation on U is a generalized left derivation on U. Further, it is shown that generalized Jordan left biderivation associated with the left biderivation on U is either U ⊆ Z(R) or a right bicentralizer on U.